2019
DOI: 10.3389/fphar.2019.01064
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Distribution of Diprotic Basic Drugs in Liposomal Systems: Perspectives on Malaria Nanotherapy

Abstract: Understanding how polyprotic compounds distribute within liposome (LP) suspensions is of major importance to design effective drug delivery strategies. Advances in this research field led to the definition of LP-based active drug encapsulation methods driven by transmembrane pH gradients with evidenced efficacy in the management of cancer and infectious diseases. An accurate modeling of membrane-solution drug partitioning is also fundamental when designing drug delivery systems for poorly endocytic cells, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…In any case, weak base trapping dictates that weak polyprotic bases like CQ and PPQ will accumulate approximately 1000-fold in the acidic environment of the parasitic DV relative to the cytosol. , Given plasma concentrations for CQ (1–10 μM) , and PPQ (100–1500 nM), , the drug concentrations used in this study to assay PfCRT-mediated drug transport correspond to concentrations of drug found within the parasite DV. These DV concentrations (which are not near the IC 50 concentrations typically measured in parasite growth inhibition assays) are the concentrations of drug to which the DV-disposed face of PfCRT that is believed to initially bind the drug is exposed .…”
Section: Discussionmentioning
confidence: 99%
“…In any case, weak base trapping dictates that weak polyprotic bases like CQ and PPQ will accumulate approximately 1000-fold in the acidic environment of the parasitic DV relative to the cytosol. , Given plasma concentrations for CQ (1–10 μM) , and PPQ (100–1500 nM), , the drug concentrations used in this study to assay PfCRT-mediated drug transport correspond to concentrations of drug found within the parasite DV. These DV concentrations (which are not near the IC 50 concentrations typically measured in parasite growth inhibition assays) are the concentrations of drug to which the DV-disposed face of PfCRT that is believed to initially bind the drug is exposed .…”
Section: Discussionmentioning
confidence: 99%
“…[72][73][74] Liposomes are used in different pathological conditions, such as cancer, inflammation, eye and skin disease, malaria, and osteosarcomas. [75][76][77][78][79][80] The liposomes can be designed using various techniques. 81,82 Overall, most liposome preparatory methods are based on (1) solvation of the lipids in an organic solvent; (2) getting lipid thin film by evaporation; (3) hydration of lipid layer by a hydrophilic solvent; (4) liposome purification (5) and characterize the properties of the final liposome.…”
Section: The Liposomementioning
confidence: 99%
“…Noteworthy, these three anti-malarial agents are polyprotic drugs that exhibit multiple ionization states and different degree of lipophilicity as a function of physiological conditions. In this context, Fernàndez-Busquets and colleagues designed distribution models that precisely describe the partitioning behaviour of these drugs in liposome vesicular systems [ 142 ]. These models have the capacity to predict the interactions of polyprotic drugs with biological and synthetic membranes depending on the pH, lipid composition and phospholipid charge.…”
Section: Liposomes As Pharmaceutical Carriers For the Prevention And Treatment Of Malariamentioning
confidence: 99%
“…These models have the capacity to predict the interactions of polyprotic drugs with biological and synthetic membranes depending on the pH, lipid composition and phospholipid charge. Importantly, these anti-malarial drug distribution modelling improved the effective drug delivery strategies such as liposome-based active drug encapsulation methods driven by transmembrane pH gradients [ 142 ].…”
Section: Liposomes As Pharmaceutical Carriers For the Prevention And Treatment Of Malariamentioning
confidence: 99%